REAGAN AT REYKJAVIK : Forty-Eight Hous That Ended the Cold War - Adelman, Ken L., (BROADSIDE BOOKS, 2014)
"A dramatic account of the historic 1986 Reagan-Gorbachev summit in Iceland--the turning point in the Cold War--by President Reagan's arms control director, a key player in that world-changing event. In October 1986, Ronald Reagan and Mikhail Gorbachev met for a forty-eight-hour summit in Reykjavik, Iceland. Planned as a short gathering to outline future talks, the meeting quickly turned to major international issues, including SDI ("Star Wars") and the possibility of eliminating all nuclear weapons. Both men were at the height of their powers, and they had a rare opportunity to move toward peace. The meeting laid the groundwork for the most sweeping arms accord in history, adopted the following year, and the end of the Soviet Union half a decade later. From his position as a participant and his skill as a historian, Adelman is able to reveal the motivations, relationships, and conversations that led to the breakthroughs. Scrupulously researched and based on now-declassified documents, Reagan at Reykjavik tells the gripping tale of that weekend, and provides an honest and up-close portrait of Reagan at one of his finest and most challenging moments"--From publisher description